STRATEGI PROTEKSI DAN PERENCANAAN PENSIUN DALAM PENGELOLAAN KEKAYAAN HNWI (HIGH NET WORTH INDIVIDUAL) BERDASARKAN TOLERANSI RISIKO - , Edo Yukamgo, Prof. Dr. Eduardus Tandelilin, M.B.A, CWM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is a case study in wealth management of HNWI (High Net Worth Individual) that having a net worth over USD 1 million or equivalent to Rp10 billion. The main requirement is the protection of clients with insurance, education planning, and retirement planning are not yet well-structured. The limitation in the client is an obstacle in the management of wealth. Limitations in the form of limited knowledge, time, and fear of risk that will be experienced when one invests. The research method used in this study is individual depth interviews with clients to determine financial statements, cash flow, needs and problems faced by clients. In addition, risk tolerance is also measured by questionnaires of Grable and Lytton (2003) by asking 13 questions. Each question has a weight that is used to calculate the risk tolerance category. From interviews with the client, we can know that the client owned assets amounted Rp17.020.900.000. The majority of these assets are allocated to physical assets, such as lands, houses and vehicles. In the cash flow analysis, can be seen that revenue comes from some sources of client business income under its management and deposits it has. After analysis, the authors developed two scenarios that are designed according to client needs and risk tolerance. Wealth Management based on three pillars, there is Wealth Protection, Wealth accumulation and Wealth Distribution. Wealth management results in first scenario can increase net worth by Rp779.607.610, second scenario can increase net worth by Rp899.794.717. Second scenario have weaknesses and strengthnesses respectively in terms of risk and return inherent in investment instruments that are recommended.